In situ, seed-free formation of a Ruddlesden–Popper perovskite Cs2PbI2Cl2 nanowires/PbI2 heterojunction for a high-responsivity, self-powered photodetector. Issue 9 (9th February 2022) - Ba, Yanshuang; Xie, Xiaoping; Zhu, Weidong; Ma, Junxiao; Liu, Gang; Dong, Peng; Chen, Dazheng; Zhang, Jincheng; Zhang, Chunfu; Hao, Yue
Abstract : The Cs2 PbI2 Cl2 nanowires/PbI2 heterojunction enlarged the built-in field ( E b ), which led to the suppressed carrier recombination and enhanced carrier transportation. The resulting device reached a specific detectivity ( D *) maximum of 3.02 × 10 12 Jones. Abstract : As the necessary precursor of emerging lead-halide perovskite materials, PbI2 is also promising for optoelectronic devices, such as photodetectors (PDs). Herein, the novel Ruddlesden–Popper (RP) perovskite Cs2 PbI2 Cl2 nanowires are grown onto PbI2 film by an in situ, seed-free solution method to build a Cs2 PbI2 Cl2 nanowires/PbI2 heterojunction, wherein the stress-induced diffusion mechanism is proposed for its formation. Furthermore, the heterojunction is used to fabricate the low-cost, simple-structure self-powered PD, which exhibits a responsivity ( R ) peak of 0.17 A W −1, a specific detectivity ( D *) maximum of 3.02 × 10 12 Jones, and a fast response speed of 0.95 μs. These performance parameters are much better than those of a similar PD based on the pristine PbI2 film and even superior to most of PbI2 -based PDs reported earlier. The greatly improved performance of the self-powered PD with the Cs2 PbI2 Cl2 nanowires/PbI2 heterojunction is largely related to the suppressed carrier recombination and enhanced carrier transportation, as a result of the enlarged built-in field ( E b ) by the heterojunction. Hence, our work provides a scientific basis for exploiting high-performance PDs by combining PbI2 with novel perovskite materials.